Serum iron as an indicator of acute inflammation in cattle - Baydar, Ersoy; Dabak, Murat (Elsevier Science Inc, 2014)
The aim of this study was to assess the value of serum iron concentration in the diagnosis of acute inflammation in cattle. The diagnostic value of this approach was compared with that of various other hematological tests, including commonly used techniques that measure the levels of various other acute-phase proteins. The study population comprised 10 cows with acute traumatic reticuloperitonitis (RPT group) and 10 cows with acute mastitis (mastitis group) admitted to the Veterinary Teaching Hospital at Firat University (Elazig, Turkey). Ten cows from local barns, kept and fed under same conditions as the diseased animals, were used as controls. After the clinical examination, blood samples were collected for biochemical, hematological, and acute-phase protein (haptoglobin, serum amyloid A, alpha-1 acid glycoprotein, and fibrinogen) analyses. The mean levels of serum iron in the RPT, mastitis, and control groups were 6.00, 7.82, and 26.78 mu mol/L, respectively. Serum iron level was significantly reduced in the RPT and mastitis groups. The results of this study indicate that serum iron analysis, preferably in combination with other markers of inflammation, may be a useful diagnostic tool for acute inflammation in cattle. Because serum iron measurement is individually available and easily applicable, it may be used for clinical cases as well as the determination of herd health.
Keywords: acute inflammation; acute-phase protein; cattle; iron